P2.043 Albumin May Influence ELISA Test Results For HIV Antibodies. (13th July 2013) - Gupta, D; Ganguly, E; Das, S
Abstract : There may be interference of albumin in binding of HIV antibodies on HIV specific antigens. This experiment has been done to find out any such possible influence of albumin which may alter the serological test results. Blood samples of known HIV positive patients were collected after taking consent. Total serum proteins were estimated, HIV antibody tests were performed with the collected samples directly and after mixing egg albumin to raise 25% of the baseline protein in each sample. The ELISA test for HIV antibodies in serums was performed with both types of samples and absorbance values were recorded. It was found that after addition of egg albumin, the absorbance values were decreased in 66.0% samples and among them in 40.0% samples there was remarkable fall of absorbance levels. In the remaining 34.0% samples there was no change in absorbance values. This study indicates that albumin present in the blood may influence outcome of ELISA test for HIV antibodies.